A novel approach to treatment of priapism refractory to non-surgical methods: A single-case experience. Issue 4 (2nd October 2019) - Abou Heidar, Nassib; Degheili, Jad A.; Bustros, Gerges; Wazzan, Wassim; Bulbul, Muhammad
ABSTRACT: Ischaemic priapism is a rarely encountered urological emergency that can lead to erectile dysfunction if not treated. Treatment strategies for ischaemic priapism include: cavernosal sympathomimetic injections; percutaneous shunts; and surgical procedures including shunts and penile prostheses. We present a case of a middle-aged man presenting with ischaemic priapism refractory to cavernosal injections and percutaneous T-shunt procedure. After refusal of surgery, a continuous cavernosal infusion of phenylephrine was successfully performed with resolution of erection and no sequelae. For the treatment of ischaemic priapism, adherence to management guidelines should be encouraged; however, it is still a disease entity that is not well understood and new treatment protocols may have a role in the future. Abbreviation : ED: erectile dysfunction